High-capacity V2N MXene for multivalent ion batteries: an Ab initio study - Saharan, Sunita; Ghanekar, Umesh; Shivankar, Bhavana R.; Meena, Shweta (Journal of Physical Chemistry C, 2024)
In this study, the electrochemical energy storage properties of V2N MXene as an electrode material for multivalent zinc (Zn2+) and calcium (Ca2+) ion rechargeable batteries have been studied using first-principles computations. Various properties like band structure, adsorption energy, diffusion kinetics, and open-circuit voltage are investigated using density functional theory. V2N MXene demonstrates metallic properties with a high structural stability and low diffusion barriers. Remarkably, Zn (976.4 mA h/g) and Ca (770.8 mA h/g)-adsorbed V2N MXene layers exhibit better storage capacity than the reported ones (517 mA h/g for zinc-intercalated CC@MnO2@Ti3C2TX and 598.63 mA h/g for calcium-intercalated V3C2/graphene). These findings make V2N MXene a highly promising cathode material for zinc and an anode material for calcium-ion batteries.